Presenting features of neuroblastoma with spinal canal invasion. A prospective study of the International Society of Pediatric Oncology Europe - Neuroblastoma (SIOPEN) - Sorrentino, Stefania; Ash, Shifra; Haupt, Riccardo; Plantaz, Dominique; Schiff, Isabelle; Hero, Barbara; Simon, Thorsten; Kachanov, Denis; Shamanskaya, Tatyana; Kraal, Katheljine; Littooij, Annemieke; Wieczoreck, Alexsandra; et al. (Frontiers in Pediatrics, 2022)
Introduction. Between 5-15% of children with neuroblastoma (NB) present with or develop spinal canal invasion (SCI). The majority of these children have symptoms of epidural compression of spinal cord and/or spinal nerves. Treatment of NB-SCI is considered an emergency but its modalities are not yet well established. Independently of treatment, NB-SCI may result in significant long-term disabilities. We report on the first prospective study of NB-SCI focused on presenting characteristics of both symptomatic and asymptomatic patients and correlation between SCI-related symptoms and imaging features. Materials and Methods. This SIOPEN prospective NB-SCI study opened in June 2014. Patient data including SCI symptoms evaluated by standardized measures and spinal cord imaging studies were collected for each patient. For the purpose of this study data entry was locked on July 2021. Results. Of the 208 NB-SCI patients registered, 196 were evaluable for this analysis of whom 67% were symptomatic and 33% asymptomatic. Median age was 11 months. The thorax was the commonest primary tumour site. The median intervals between initial symptoms and diagnosis and between first medical visit and diagnosis were 14 and 3 days, respectively. The was no statistical difference in frequency of presenting characteristics between symptomatic and asymptomatic patients. Presenting features of NB-SCI patients differed from other NBs for older median age, prevalence of thoracic versuss abdominal primary site, prevalence of localized versus metastatic disease and lower incidence of MYCN gene amplification. The most common SCI features were motor deficit in the younger and pain in the older patients that correlated on imaging with both transverse and longitudinal extent but not with the level of intraspinal tumour. Spinal cord T2-hyperintensity was more frequently detected in symptomatic patients (not significant). Conclusions. This prospective study confirms that children with NB-SCI differ from NBs without SCI. Compared to previous studies, it provides more detailed information regarding presenting symptoms, time intervals between SCI symptoms, medical visit and diagnosis, and correlations between symptoms and imaging features.